Artificial Neural Network Model In Forecasting Post-Covid-19 Aviation Business Development Using Multi Layer Perceptron (MLP) - Romani, Daniel D.; Nasution, Darmeli; Syahputra, Afandi; Usman, Usman; Prayitno, Hadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Aviation business forecasting is one way to find out the next steps that must be taken by aviation business actors as well as steps that the government must take to improve the country's economy, especially from the air transportation sector. before the covid-19 pandemic, the global aviation industry experienced a positive trend, where the volume of global passenger flow in december 2019 increased by 4.9% based on the calculation of revenue passenger kilometers, but since covid-19 began to emerge in early 2020, the movement the global rpk experienced a drastic decline until march 2020, then from april 2020 it experienced an increasing trend again, but lower than in 2019. To be able to provide recommendations for industry players aviation for study material and policy implementation to continue to improve flight performance, especially in Indonesia. MLP is also able to show better performance than the classic arima model. In this study, the mlp model will be used to forecast post-covid-19 flight conditions which will provide research results about the description of the condition of the aviation industry for the future, especially in responding to the challenges of the post-covid-19 aviation industry. to be able to provide recommendations for industry players aviation for study material and policy implementation to continue to improve flight performance, especially in indonesia.